2019
DOI: 10.1136/bcr-2019-230056
|View full text |Cite
|
Sign up to set email alerts
|

Primary cytomegalovirus infection with invasive disease in a patient with inflammatory bowel disease

Abstract: A 37-year-old woman with a history of inflammatory bowel disease on mercaptopurine presented with a week of recurrent fever, headache, myalgias and mildly elevated serum transaminases and leucopenia. Her workup revealed primary cytomegalovirus (CMV) infection with atypical lymphocytosis, elevated viral load, positive IgM and negative IgG. Two weeks after her initial presentation, she developed odynophagia and diarrhoea prompting endoscopic evaluation with biopsies, which demonstrated CMV disease of the gastroi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Furthermore, CMV infection can present in various ways. Besides CMV pneumonitis, several case reports showed that immunosuppressive therapy might have a role in development of CMV retinitis [ 13 , 14 ], as well as thrombocytopenia [ 15 ], myalgia [ 16 ], arthralgia [ 17 , 18 ], hepatitis [ 19 ], pericarditis [ 20 ], or gastrointestinal [ 8 , 10 ] and neurological disorders [ 19 , 21 ], and even oral ulcers [ 22 , 23 ]. In some rare cases, CMV infection also presents as nephrotic syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, CMV infection can present in various ways. Besides CMV pneumonitis, several case reports showed that immunosuppressive therapy might have a role in development of CMV retinitis [ 13 , 14 ], as well as thrombocytopenia [ 15 ], myalgia [ 16 ], arthralgia [ 17 , 18 ], hepatitis [ 19 ], pericarditis [ 20 ], or gastrointestinal [ 8 , 10 ] and neurological disorders [ 19 , 21 ], and even oral ulcers [ 22 , 23 ]. In some rare cases, CMV infection also presents as nephrotic syndrome.…”
Section: Discussionmentioning
confidence: 99%